Surveillance of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) in high-rise apartment buildings in Selangor, Malaysia - Muhammad Aidil, Roslan; Romano, Ngui; Indra, Vythilingam; Kien, Fatt Chan; Poo, Soon Ong,; Ching, Keat Low; Nur Hidayah, Muhammed; Wan Yusoff, Wan Sulaiman (Springer Nature, 2022)
Dengue is a mosquito-borne disease that causes high mortality and fatality rate among humans. The disease and the virus are spread through female Ae. aegypti and Ae. albopictus. 176 Modified Sticky Ovitraps (MSO) were installed in six blocks of high-rise apartment buildings in Petaling Jaya, Selangor. The specimens were collected throughout a duration of 26 weeks. NS1 dengue antigen kit was used to detect dengue antigen in mosquitoes, and positive mosquitoes were serotyped using Reverse Transcriptase-PCR, followed by Multiplex-PCR. The relationship between the number of Aedes mosquitoes and meteorological parameters was also determined. The association between the number of Aedes spp. captured, dengue cases, and positive specimens was also evaluated in this study. A total of 243 adult mosquitoes were successfully captured using MSO, with 95.1% (231) of the mosquitoes being Ae. aegypti, while 4.1% (10) and 0.8% (2) were Ae. albopictus and a mixed Aedes species, respectively. The molecular detection of the dengue virus showed that only 2 individual specimens of Ae. aegypti were positive, with one specimen being a dual serotype of DEN-II and IV, and another specimen was DENV-II. The weekly number of Aedes spp. captured correlated positively with Tmax, Tmin, and Tmean, and correlated negatively with RF and RH. The significant and useful data obtained from this study can be utilized in dengue vector management by local health authorities.